2014
DOI: 10.1111/adb.12151
|View full text |Cite|
|
Sign up to set email alerts
|

Sleep changes in smokers before, during and 3 months after nicotine withdrawal

Abstract: Nicotine may affect sleep by influencing sleep-regulating neurotransmitters. Sleep disorders can increase the risk for depression and substance dependency. To detect the influence of sleep disturbances on the effect of smoking cessation, we investigated polysomnographically (PSG) the sleep of smoking subjects during a period of smoking, during withdrawal and after a period of abstinence from nicotine. Thirty-three smokers (23 male, 10 female, median age 29 years, Fagerström Test for Nicotine Dependence score 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 34 publications
4
40
1
4
Order By: Relevance
“…This relationship was further examined in a study by Jaehne et al . (), who investigated using polysomnograph recordings and subjective ratings the sleeping patterns of smokers during periods of smoking and withdrawal (24–36 hours after smoking cessation) and after a period of nicotine abstinence (3 months after cessation). The authors demonstrated that nicotine withdrawal resulted in increased arousal and wake time as compared to the smoking state.…”
Section: Human Studiescontrasting
confidence: 66%
“…This relationship was further examined in a study by Jaehne et al . (), who investigated using polysomnograph recordings and subjective ratings the sleeping patterns of smokers during periods of smoking and withdrawal (24–36 hours after smoking cessation) and after a period of nicotine abstinence (3 months after cessation). The authors demonstrated that nicotine withdrawal resulted in increased arousal and wake time as compared to the smoking state.…”
Section: Human Studiescontrasting
confidence: 66%
“…7 Consequently, sleep disturbances have been observed among nicotine-dependent individuals. [8][9][10] Short sleep duration has been linked with an increased risk of morbidity and mortality. 8,[11][12][13][14] Based on self-reported smoking, current smokers have been found to have higher odds of short sleep duration and poor sleep quality compared to neversmokers.…”
Section: Introductionmentioning
confidence: 99%
“…Smoking abstinence of such older adults led to impairments in sleep quality, reflected by increased number of sleep stage changes, awakenings, and arousal [29] or sleep fragmentation [30] following the first 48-72 hours of abstinence [31]. More recently, Jaehne and colleagues [32,33] reported similar results in a sample that included young adults alongside older adults (median age of group: 29; range: ). Yet, the authors did not report analysis of sleep quality by age group.…”
Section: Journal Of Sleep Disorders and Therapymentioning
confidence: 81%